Impact of DISC1 variation on neuroanatomical and neurocognitive phenotypes - Carless, M; Glahn, D; Johnson, M; Curran, J; Bozaoglu, K; Dyer, T; Winkler, A; Cole, SA; Almasy, L; MacCluer, J; Duggirala, R; Moses, E; et al. (Nature Publishing Group, 2011)
Although disrupted in schizophrenia 1 (DISC1) has been implicated in many psychiatric disorders, including schizophrenia, bipolar disorder, schizoaffective disorder and major depression, its biological role in these disorders is unclear. To better understand this gene and its role in psychiatric disease, we conducted transcriptional profiling and genome-wide association analysis in 1232 pedigreed Mexican-American individuals for whom we have neuroanatomic images, neurocognitive assessments and neuropsychiatric diagnoses. SOLAR was used to determine heritability, identify gene expression patterns and perform association analyses on 188 quantitative brain-related phenotypes. We found that the DISC1 transcript is highly heritable (h2=0.50; P=1.97 × 10−22), and that gene expression is strongly cis-regulated (cis-LOD=3.89) but is also influenced by trans-effects. We identified several DISC1 polymorphisms that were associated with cortical gray matter thickness within the parietal, temporal and frontal lobes. Associated regions affiliated with memory included the entorhinal cortex (rs821639, P=4.11 × 10−5; rs2356606, P=4.71 × 10−4), cingulate cortex (rs16856322, P=2.88 × 10−4) and parahippocampal gyrus (rs821639, P=4.95 × 10−4); those affiliated with executive and other cognitive processing included the transverse temporal gyrus (rs9661837, P=5.21 × 10−4; rs17773946, P=6.23 × 10−4), anterior cingulate cortex (rs2487453, P=4.79 × 10−4; rs3738401, P=5.43 × 10−4) and medial orbitofrontal cortex (rs9661837; P=7.40 × 10−4). Cognitive measures of working memory (rs2793094, P=3.38 × 10−4), as well as lifetime history of depression (rs4658966, P=4.33 × 10−4; rs12137417, P=4.93 × 10−4) and panic (rs12137417, P=7.41 × 10−4) were associated with DISC1 sequence variation. DISC1 has well-defined genetic regulation and clearly influences important phenotypes related to psychiatric disease.